BUSINESS ANALYSIS, DISTRIBUTION AND INCOME CONTRIBUTION OF THATCH LEAF ROOF WEAVERS IN THATCH LEAF ROOFING BUSINESS IN BLANG CUT VILLAGE PEUSANGAN DISTRICT BIREUEN REGENCY - Elyza Elyza; Eva Wardah; Emmia Tambarta Kembaren; Setia Budi (Jurnal Mahasiswa Agribisnis, 2024)
The presence of the thatch leaf woven roof agroindustry in the midst of rural community life is aimed at expanding employment opportunities for the surrounding community and can increase the income of entrepreneurs and weavers. Mr. Syukri's thatched roof woven business, located in Blang Cut Village, Peusangan District, Bireuen Regency, which was built in 2011, is a small business that has developed the potential of natural resources through weaving thatched leaves into house roofs. The roof made from thatch definitely increases the income of the weavers which can be used to meet household needs. This research aims to analyze the business, distribution and contribution of thatch leaf roof weavers' income to family income. This research uses primary data and secondary data. The data analysis method used is quantitative analysis using the Gini index analysis tool. The results of the research show that the profit obtained in one production process in Mr Syukri's thatched roof woven business is IDR 14.409.253/production. Meanwhile, the average income of thatch leaf roof weavers is IDR. 229.076 / month. The income distribution of thatch leaf roof weavers is at a low level of income inequality with a Gini Ratio Index of 0,09, which means that the income of thatch leaf roof weavers is fairly evenly distributed to meet household needs. The contribution of thatch leaf roof weavers' income to family income is 16,42%, meaning that the contribution of thatch leaf roof woven craftsmen's income to the income of small families is ‰¤ 50%. Keywords: business analysis, income contribution, income distribution, leaf roofing